Pietroburghesi in viaggio: cultura popolare ed etnografia urbana - Emilio Mari (eSamizdat)
The transformation process of Petersburg into an industrial metropolis has produced, in the collective imaginary as well as in the practicalities of everyday life, on the one hand a progressive fragmentation and hierarchisation of interior spaces, and on the other, a general reconsideration of the dualism city vs non-city. With the development of long-distance and suburban rail networks, space and time suddenly experienced a condensation, and what once could be reached only at the cost of a long, arduous and risky immersion into the uneven and inhospitable rural/provincial landscape was now within the citizen's reach. Within a few decades, the exploration of the "other" space changed from being a privilege for the elites to a mass cultural phenomenon, a practice of identification for the new urban lower-middle class. The aim of this paper is to retrace how this new concept of tourism – antithetical to the old aristocratic Grand Tour – took shape: a tourism whose aim was to encounter "internal" and "intrasystemic" otherness, nestled away in the folds of industrial modernity, in the crevices of a deeply stratified and heterogeneous landscape.